Species complex of mosquitos captured by mechanical traps and an equine host - Clinton B Campbell; Daniel L Kline; Jerome A Hogsette; Saundra H TenBroeck (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Field studies were conducted to evaluate the efficacy of commercially available mosquito traps to capture suspected West Nile Virus (WNV) vectors and compare the relative abundance, and species composition of mosquitoes captured by traps. Traps included the Mosquito Magnet (MM) Pro, MM-Liberty, MM-X, the CDC-1012, and the Home and Garden (HGM) prototype trap. In the first study, conducted at the University of Florida Horse Teaching Unit (HTU), Gainesville, FL, from May 17 to September 30, 2002, the CDC-1012 caught significantly more mosquitoes than the other traps. The HGM trap did not catch any mosquitoes and was replaced with a horse on July 17. Percentages of WNV vector species captured in traps and vacuumed from the horse, respectively, were Culex nigripalpus Theobald 85-91% and 27%, and Mansonia titillans (Walker) 2-5% and 40%. In the second study, performed for 5 days in April 2003, the MM-Pro, MM-X, and CDC-1012 traps caught significantly more mosquitoes than did the MM-Liberty trap. All traps captured primarily Cx. salinarius Coquillett, Cx. erraticus (Dyar and Knab), and Anopheles crucians Wiedemann. The horse attracted a greater percentage of Ma. titillans and less Cx. erraticus than did the mechanical traps. The mechanical traps may offer horses some degree of protection from suspected WNV species, however, a large number of Ma. titillans were recovered from the horse but the traps captured very few.